2013
DOI: 10.1371/journal.pone.0058196
|View full text |Cite
|
Sign up to set email alerts
|

IL-23 Induces Atopic Dermatitis-Like Inflammation Instead of Psoriasis-Like Inflammation in CCR2-Deficient Mice

Abstract: Psoriasis is an immune-mediated chronic inflammatory skin disease, characterized by epidermal hyperplasia and infiltration of leukocytes into the dermis and epidermis. IL-23 is expressed in psoriatic skin, and IL-23 injected into the skin of mice produces IL-22-dependent dermal inflammation and acanthosis. The chemokine receptor CCR2 has been implicated in the pathogenesis of several inflammatory diseases, including psoriasis. CCR2-positive cells and the CCR2 ligand, CCL2 are abundant in psoriatic lesions. To … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 67 publications
(98 reference statements)
0
21
0
Order By: Relevance
“…Thus, up-regulation of IL-20 may contribute to the proliferation of keratinocytes and development of a thickened epidermis (hyperkeratosis) and the scaly and crusted skin associated with advanced scabies. IL-23 is produced in excess in psoriatic skin [39][44]. In vivo , IL-23 is produced by keratinocytes and dendritic cells and its effect in skin pathology is mediated by Th17 cytokines [44].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, up-regulation of IL-20 may contribute to the proliferation of keratinocytes and development of a thickened epidermis (hyperkeratosis) and the scaly and crusted skin associated with advanced scabies. IL-23 is produced in excess in psoriatic skin [39][44]. In vivo , IL-23 is produced by keratinocytes and dendritic cells and its effect in skin pathology is mediated by Th17 cytokines [44].…”
Section: Discussionmentioning
confidence: 99%
“…[23][24][25][26] Furthermore, the IL-23-injected mouse model, which has been traditionally considered to resemble psoriasis 27,28 and exhibits the largest (25%) transcriptomic homology with human psoriasis fingerprinting among existing ''psoriasis-like'' models, 29 has also been found to display T H 2 activation and simulate AD-like skin inflammation. 30 Although all murine AD-like models (with the exception of Flg-mutated mice) 16,[18][19][20]22,24,27 are visibly inflamed, it is difficult to macroscopically differentiate AD-like dermatitis in mice from lesions mimicking contact dermatitis (CD) or psoriasis. For example, because flaky tail mice exhibit T H 17-dominated skin inflammation, 31,32 this murine model might more closely simulate a psoriasis-like phenotype rather than AD-like fingerprinting.…”
Section: Abbreviations Usedmentioning
confidence: 99%
“…AD may depend on the presence or absence of specific cytokines (49). More recently, Bromley et al (50) showed that the chemokine (c-c motif) receptor 2-deficient mice which were injected intradermally with IL-23, a cytokine that increases the expression of IL-17 and IL-22 that characterize psoriatic lesions, developed skin lesions that resembled AD with elevated number of eosinophils and increased expression of IL-22, TSLP, and IL-4. The study did not find increased infiltration of Th2 cells in the lesions, suggesting that IL-22 may provide feedback to innate cells to increase allergic inflammation, rather than antimicrobial response, in chemokine (c-c motif) receptor 2-deficient mice.…”
Section: Pathogenesis Of Atopic Dermatitismentioning
confidence: 99%